PENGENDALIAN SOSIAL PELANGGARAN TATA TERTIB MEROKOK PADA SANTRI DI PONDOK PESANTREN DARUL KHAIRAT PONTIANAK - Yessir, Yessir; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this study is "Social Control of Violations of Smoking Rules on Santri at the Pontianak Darul Khairat Islamic Boarding School". The first sub problem is how preventive forms of social control, both how forms of repressive social control and coercive social control in tackling smoking violations in santri in the darul khairat pontianak boarding school The approach used in this study is a qualitative approach with descriptive methods. The results of this study prove that the form of social control applied in the Darul Khairat Islamic boarding school consists of three. Preventive control is carried out by means of socialization. During salafiyah learning as well as socialization by attaching the pesantren's order in open areas such as mading and also advising and reprimanding on repressive social control carried out by calling parents and warning letters, but if there is still no deterrent effect, then in a coercive manner, namely the punishment and sanctions such as cleaning the environment of the pesantren and with the sanction of hair shaving also in the hope that it can become obedient in the pesantren.        Keywords: Social Control, Violation of Rules, Santri